2012
DOI: 10.1590/s0100-29452012000400026
|View full text |Cite
|
Sign up to set email alerts
|

Constituintes químicos das frações de lichia in natura e submetidas à secagem: potencial nutricional dos subprodutos

Abstract: A lichieira (Litchi chinensis Sonn.) é uma planta da família das Sapindáceas, perfeitamente adaptada às condições climáticas brasileiras e pouco estudada quanto à composição química de seus frutos, sobretudo das frações casca e semente, frequentemente descartadas pela indústria e consumidores. Objetivou-se com este trabalho determinar os constituintes químicos das frações casca, polpa e semente in natura, e da casca e semente submetidas à secagem a 45ºC. Cada fração foi avaliada em sete repetições (de 20 fruto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 11 publications
4
7
0
12
Order By: Relevance
“…The pH values close to 4.5 can prevent the growth of microorganisms (Queiroz et al, 2012). The pH value found for the papaya peel flour in both cultivars was close to 4.5.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The pH values close to 4.5 can prevent the growth of microorganisms (Queiroz et al, 2012). The pH value found for the papaya peel flour in both cultivars was close to 4.5.…”
Section: Resultsmentioning
confidence: 63%
“…The content of soluble solids is an indicative of the contents of soluble sugars present in foods, and therefore of their sweetness, and it is influenced by many factors, such as cultivar, climate, and soil among others (Queiroz et al, 2012). For this variable, higher values of the peel flour (5.75 and 6.0 °Brix) were obtained, and they are lower than those reported by Rinaldi et al (2010), who observed contents between 8.1 and 9.9 °Brix for the cultivars Formosa and Papaya.…”
Section: Resultsmentioning
confidence: 99%
“…Tailandes was slightly lower to cv. Bengal, which is widely cultivated in Brazil (21 g to 23 g) [5,8]. However, the cultivar analyzed in this study had a higher pulp yield than fruits of cv.…”
Section: Physical Characterizationmentioning
confidence: 66%
“…Different cultivars of lychee are produced all around the world. The cultivar Mauritius stands out in South America, the cultivar Groff in the United States and China, and the cultivar Bengal in Brazil [1,5,[8][9][10][11]. Information on the nutritional value, especially vitamins and minerals, of these lychee cultivars is rare in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse contexto, de acordo com Queiroz et al (2012), o uso de alimentos alternativos para o combate a fome é objeto de atenção no Brasil, principalmente pelos altos índices de desnutrição observados nos últimos anos.…”
unclassified